A Periodic Wetting Surface Driven by Triboelectric Nanogenerator for Efficient Postimpact Droplet Collection. Issue 2 (20th November 2022) - Tan, Jie; Fan, Zeng; Sun, Shulan; Xu, Minyi; Jiang, Dongyue
Abstract: The phenomenon of droplet impact is widely observed in nature and industrial processes. No matter the intrinsic wettability (hydrophobic, hydrophilic, and superhydrophobic) of the surface, the postimpact droplets tend to rebound or splash. The droplet impact dynamics have been well investigated but the inhibition of the rebounding or splashing of the postimpact droplet requires further exploration. This paper proposes a periodic wetting surface (PWS) driven by a triboelectric nanogenerator (TENG) for efficient postimpact droplet collection. With the high‐voltage electric signal generated from a rotating freestanding triboelectric nanogenerator (RF‐TENG), the wettability of an interdigital electrodes‐based electrowetting‐on‐dielectric (EWOD) surface can be changed periodically. The droplet impacts on the PWS show oscillating sliding motion that compensates the kinetic energy for droplet rebounding or splashing. As compared to pure hydrophobic or hydrophilic surfaces, the PWS shows the best droplet collection performance. The effects of the electric signal of the RF‐TENG such as open‐circuit voltage (0.44–3.00 kV) and frequency (0–60 Hz), droplet contents such as ions type and concentration of the droplet on the postimpact droplet collection efficiency are discussed. Finally, a practical application is demonstrated by the TENG driven PWS for real‐time and high‐efficiency collection of multiple postimpact droplets. Abstract : This study proposes a periodically wetting surface (PWS) for collecting postimpact droplets. Using TENG as the power supply, the PWS surface can realize temporal wettability variation for compensating the rebound momentum of the impact droplet and achieve rebound inhibition effect. This phenomenon is different from droplet impacts on hydrophobic, hydrophilic, and superhydrophobic surfaces.